Pengaruh Usability Information Quality Service Interaction Quality Terhadap Kepuasan Pengguna Google Scholar - Ramasari, Amidita; Ardellia, Raissa Davina; Oktaviana, Ferra Ramadhan; Prestianissa, Assyifa Lucky; Arlyansyah, Aprilla Agatha; Putri, Chelsea Hutami (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) UGP, 2025)
In the digital learning era, students increasingly rely on academic platforms like Google Scholar due to its ease of access to literature. This study examines the effects of usability, information quality, and service interaction quality on user satisfaction among students of the Faculty of Social and Political Sciences, Universitas Airlangga. Using a descriptive quantitative approach, data were collected from 114 students via an online survey and analyzed using multiple linear regression in Jamovi. Results show that usability and service interaction quality significantly influence satisfaction, while information quality does not. Together, these variables explain 46.1% of the variance. The findings highlight the importance of intuitive user experience and interactive service in shaping satisfaction with academic search platforms. This study offers insights for digital service providers and educational institutions.